A survival case of amlodipine poisoning - Rathore, Abhishek; Ranjan, Nitish K; Sadananda, Kanchanahalli Siddegowda; Basappa, Harsha; Manjunath, Cholenahally Nanjappa (Indian Journal of Case Reports, 2020)
Calcium channel blockers are commonly used in various cardiovascular diseases, but its poisoning may lead to fatal outcomes. We report a case of alleged poisoning of amlodipine in a 25-year-old female who consumed 20 tablets of 5 mg amlodipine. She presented with cardiogenic shock, hypoglycemia, hypokalemia, constipation, and central nervous system symptoms which were managed with intravenous crystalloids, calcium gluconate, 5% dextrose, dopamine, and noradrenaline infusion after which patient responded well and discharged.